IT Laws in the Era of Cloud-Computing A Comparative Analysis between EU and US Law on the Case Study of Data Protection and Privacy - Kontargyris, Xenofon (Nomos Verlagsgesellschaft mbH & Co. KG, 2018)
This book documents the findings and recommendations of research into the question of how IT laws should develop on the understanding that today's information and communication technology is shaped by cloud computing, which lies at the foundations of contemporary and future IT as its most widespread enabler. In particular, this study develops on both a comparative and an interdisciplinary axis, i.e. comparatively by examining EU and US law, and on an interdisciplinary level by dealing with law and IT. Focusing on the study of data protection and privacy in cloud environments, the book examines three main challenges on the road towards more efficient cloud computing regulation:-understanding the reasons behind the development of diverging legal structures and schools of thought on IT law-ensuring privacy and security in digital clouds-converging regulatory approaches to digital clouds in the hope of more harmonised IT laws in the future.